Digital Communication Instagram Account @Monumenpers During the Covid-19 Pandemic - Wijaya, Niken; Pawito, Pawito; Rahmanto, Andre N. (Universitas Sebelas Maret, 2022)
Digital communication during the covid-19 pandemic is needed because of social distancing regulations and the closure of public services, one of which is the National Press Monument. One form of digital communication is through social media platforms. During the pandemic, the Instagram account @monumenpers became the main media channel for disseminating information and communication facilities for the National Press Monument with the public. The purpose of this study is to provide an understanding of the digital communication process for the Instagram @monumenpers account. The research method used is an interpretive qualitative research method with qualitative content analysis techniques confirmed by interviews with key informants. The theory used in this study is the Circular of SOME model by Regina Luttrell. The communication process is explained through the four components of The Circular of SOME model by Regina Luttrell, namely share, optimize, manage and engage. The findings show that the digital communication process for the @monumenpers Instagram account during the covid-19 pandemic involved the National Press Monument social media management team (communicators) and the public/followers (communicants). Content material and information dissemination activities and responses are carried out by the Instagram account admin/management team and interactions occur with followers. High levels of engagement on certain content, one of which is content about the giveaway program.